THE IMPORTANCE OF MODERN METHODS IN TEACHING BIOLOGY - Mirzobek Qurambayev Ulug’bekovich (Galaxy International Interdisciplinary Research Journal, 2021)
The article discusses the importance of modern methods of teaching biology and the importance of interactive methods in the modern education system.